Mental Health Disturbances and Related Problems in Italian University Medical Students from 2000 to 2020: An Integrative Review of Qualitative and Quantitative Studies - Sampogna, Gaia (Medicina (Kaunas), 2020)
Background and objectives: The presence of mental health problems in the population of medical students in Italy has been evaluated in several cross-sectional studies, which have used different methodologies and study designs. However, a global overview of the prevalence of mental health problems in Italian medical students is not available, although this would be essential for promoting preventive strategies and supportive treatments. Materials and Methods: An integrative review aiming to describe the prevalence of mental health problems in Italian medical students has been performed. Results: The most relevant findings are the high prevalence of substance use, in particular alcohol and nicotine, and of depressive and anxiety disorders in Italian medical students. In particular, substance use ranges from 13 to 86%, which is higher compared to Italian students coming from other faculties. Italian medical students show a high rate of smoking and of depressive symptoms of about 20%. Conclusions: Our findings highlight the need to develop appropriate supportive interventions for the medical student population, which are rarely provided and implemented among the routine activities of Italian medical universities. A relevant aspect to be considered is the stigma and anticipated discrimination attached to mental disorders, which reduce the help-seeking process in medical students.